2009
DOI: 10.1021/tx900090m
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Agent Analogues That Produce Authentic Soman, Sarin, Tabun, and Cyclohexyl Methylphosphonate-Modified Human Butyrylcholinesterase

Abstract: The goal was to test 14 nerve agent model compounds of soman, sarin, tabun, and cyclohexyl methylphosphonofluoridate (GF) for their suitability as substitutes for true nerve agents. We wanted to know whether the model compounds would form the identical covalent adduct with human butyrylcholinesterase that is produced by reaction with true nerve agents. Nerve agent model compounds containing thiocholine or thiomethyl in place of fluorine or cyanide were synthesized as Sp and Rp stereoisomers. Purified human but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…For complexes of P R organophosphates and hCE1, we propose that they remain at the acyl-enzyme intermediate stage of the enzyme's reaction mechanism. This state has been observed in the hCE1-P R soman and hCE1-P R cyclosarin crystal structures and via matrix-assisted laser desorption ionization/time of flight analysis of BuChE inhibited by P R analogs of sarin, soman, and cyclosarin (Gilley et al, 2009). For the 40% of P S -sarin analog complexes with hCE1 that do not undergo reactivation, we propose that an alternate Ser221 state is created.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…For complexes of P R organophosphates and hCE1, we propose that they remain at the acyl-enzyme intermediate stage of the enzyme's reaction mechanism. This state has been observed in the hCE1-P R soman and hCE1-P R cyclosarin crystal structures and via matrix-assisted laser desorption ionization/time of flight analysis of BuChE inhibited by P R analogs of sarin, soman, and cyclosarin (Gilley et al, 2009). For the 40% of P S -sarin analog complexes with hCE1 that do not undergo reactivation, we propose that an alternate Ser221 state is created.…”
mentioning
confidence: 52%
“…5). These analogs have been shown by matrix-assisted laser desorption ionization/time of flight mass spectrometry to yield, among other products, acyl-enzyme adducts identical with those from authentic agents when used to inhibit butyrylcholinesterase (Gilley et al, 2009). The thiomethyl-leaving group that replaces the fluoride atom found in nerve agents decreases the toxicity of the analogs by slowing the rate of phosphonylation (k 2 ) compared with real agents; however, the dissociation constants (K d ) remain similar (Forsberg and Puu, 1984).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These analogs have been previously shown to form adducts identical to authentic agents. 13,14) This second-order inhibition constant (k i ϭk 2 /K m ) can be broken down into individual components. The rates of phosphonylation (k 2 ) between P R and P S isomers were similar, while the binding constants (K m ) differed by at least three-orders of magnitude (Fig.…”
Section: Substrate Bindingmentioning
confidence: 99%
“…In this article, we describe the development and validation of a novel screening method that identified hBChE variants with a decreased rate of inhibition by OPs. Because the use of chemical warfare agents is strictly regulated, we used nerve-agent model compounds that have been shown to have similar functional properties to authentic OP compounds (Barakat et al, 2009;Gilley et al, 2009). OP model compounds not only served as a useful means for screening hBChE variants in molecular evolution screening, but also were used in kinetic studies of variants identified (Ralph et al, 2011).…”
Section: Introductionmentioning
confidence: 99%